Post-COVID-19 syndrome rehabilitation protocol in primary care (Research, Society and Development, 2022)
Objective: Application and analysis of a physiotherapeutic protocol for the rehabilitation of post-COVID-19 syndrome in primary care. Methodology: Interventional and transversal clinical research, carried out at the Margarida Santos da Silva health center and at the Dr. José Archimedes Pedroso Meloni. 59 volunteers with post-COVID-19 syndrome aged 18 to 78 years were selected, who were interviewed for anthropometric data collection, concomitant pathologies, medication use, pulse oximetry, systemic blood pressure (BP), 6-minute walk test. Symptom and general status assessment scales such as: Edmonton Symptom Assessment System Revised (ESA-r), Post-COVID-19 Functional Status Scale (PCFS) were applied, as well as specific instruments for pain, fatigue and dyspnea assessment: McGill Scale, Pulmonary Questionnaire Functional Status and Dyspnea (PFSDQ), Visual Analog Scale, Barthel Index, Medical Research Council Scale (mMRC), Baseline Dyspnea Index, Borg Scale. Statistical method: Categorical variables were described using raw frequencies and percentages. Continuous variables were described using median and interquartile range, Shapiro-Wilks, Wilcoxon, Rank-Biserial, with a significance level of 5%. Conclusion: The protocol proved to be safe and feasible in primary care, and can be performed with post-COVID-19 patients. Therefore, it can be applied, respecting the individualities of the syndrome, to meet the needs of each patient. The entire protocol must consider the comorbidities that may affect the clinical course and, in this regard, we suggest a multidisciplinary approach in the training and application of the protocol.